Dead or alive - Clancy, Tom (New York Berkley Books, 2012)
Jack Ryan, Jr. and his Campus colleagues John Clark and Ding Chavez, go after a vicious terrorist mastermind--the Emir--and they will bring him in ... dead or alive
1
Keywords: Terrorism -- Prevention -- Fiction